Comparative In Vitro Anthelmintic Activity Of Chloroform And Acetone Extracts Of Mentha Piperita - S, Rekha (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTPeppermint is a hybrid mint, a cross between the water mint (Mentha aquatica) and spearmint (Mentha spicata). Different commercial preparations exhibit various activities. Peppermint oil and menthol have moderate antibacterial effects against both Gram-positive and Gram-negative bacteria. Chloroform and acetone extracts of the plant Mentha Piperita were investigated for their anthelmintic activity against Pheritima posthuma. Each extract was studied at 20 mg/ml, which involved determination of time of paralysis and time of death of the worms. Both the extracts of the plant exhibited considerable anthelmintic activities, and the order of sensitivity of the extracts to the worms was that chloroform extract of M. piperita showed the best anthelmintic activity when compared with acetone extract. Albendazole (20 mg/ml) and distilled water were included in the assay as standard reference drug and control, respectively.